A Cybernetic Analysis of Maximum Unnoticeable Added Dynamics for Different Baseline Controlled Systems. Issue 1 (July 2017) - Matamoros, I.; Lu, T.; Paassen, M.M. van; Pool, D.M.
Abstract: Maximum unnoticeable added dynamics (MUAD) envelopes have been largely used to assess the adequacy of low-order equivalent systems (LOES) in handling qualities assessment and simulator validation. However, research has shown that more thorough verification of the adequacy of this method is required. This paper studies the influence of the baseline aircraft dynamics on the MUAD envelopes. The assessment is based on quantitative measures of pilot control behaviour obtained with the cybernetic approach. The measures were taken from a human-in-the-loop pitch tracking task experiment with compensatory display. The results are consistent with the MUAD envelopes and reveal no interaction effects of the baseline and added dynamics on the pilot control behaviour. This suggests that, under the considered conditions, the MUAD envelopes shall remain constant independently of the bandwidth of the baseline controlled dynamics.